Indium-like film-forming coating

JP2024175246AActive Publication Date: 2024-12-18FECT
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023092864
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-06
Publication Date
2024-12-18
Estimated Expiration
2043-06-06

AI Technical Summary

Technical Problem

Existing metallic coating films using scaly indium particles fail to achieve the desired brightness level of a dull chrome plating appearance, and methods incorporating silver nanoparticles instead of scaly indium result in a loss of indium tone.

Method used

A paint formulation combining scaly indium particles with silver nanoparticles, a polymer dispersant, and a volatile alcohol solvent, with a mass ratio of indium to silver between 3% and 50%, maintains the dull chrome plating appearance while enhancing brightness.

Benefits of technology

The combination achieves a higher gloss value and lightness (L* value) in the coating film, maintaining the indium tone and providing improved brightness without excessive cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide an indium-like film-forming coating capable of forming an indium-like film with high luminance and excellent mirror-like aesthetics.SOLUTION: An indium-like film-forming coating according to the present invention comprises flaky indium fillers, silver nanofillers, a polymer dispersant, and a volatile alcohol solvent. The content of the silver nanofillers to the flaky indium fillers is preferably 3% or more and 50% or less in mass ratio, more preferably 10% or more and 40% or less in mass ratio. Examples of the alcohol solvent can include one or more selected from the group consisting of methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-methyl-1-propanol, and 1-methoxy-2-propanol.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a paint for forming an indium-toned coating film that can form an indium-toned coating film with excellent mirror-finish design properties, and in particular to a paint for forming an indium-toned coating film that can form an indium-toned coating film with high brightness and excellent mirror-finish design properties. [Background technology]

[0002] Traditionally, in order to increase the product appeal of interior and exterior parts of automobiles, and the housings of mobile phones, laptops, home appliances, etc., paint has been applied to the products to enhance their design. However, in recent years, it has also become common to use a mirror-like design with a texture similar to that of a mirror to further increase the distinctiveness of the product.

[0003] Known methods for imparting mirror designs include (i) plating, (ii) vapor deposition (physical thin film deposition (PVD) methods such as sputtering and ion plating, and chemical thin film deposition (CVD) methods), and (iii) silver mirror coating, each of which has its advantages and disadvantages. (i) Plating has a high environmental impact in terms of wastewater treatment, etc., requires special equipment, has many steps, and is disadvantageous in terms of manufacturing efficiency and cost. (ii) PVD and CVD methods require special equipment for vapor deposition processing, which is large-scale and disadvantageous in terms of installation costs. (iii) Silver mirror coating may require wastewater treatment, etc. depending on the paint ingredients, but it can be formed using a general coating method, so it does not require special equipment and has low installation costs.

[0004] Known coating methods for imparting metallic luster include dispersing metal particles such as gold, silver, and aluminum in paint or dispersing these metal particles themselves in aqueous or non-aqueous solvents. These methods have been used to form coating films with metallic designs on surfaces of plastics, glass, ceramics, and even wood. While gold and silver are excellent metals for creating metallic designs, they are expensive precious metals, and aluminum flakes have traditionally been used as luster materials. However, because aluminum flakes have particle sizes on the order of micrometers, the graininess of the aluminum flakes remains on the coating surface, resulting in insufficient color clarity and gloss, preventing the creation of a bright silver mirror gloss surface like that of a silver mirror coating. Furthermore, they may react with water to generate hydrogen gas. Therefore, indium, which is water-stable and non-toxic and offers a unique metallic design, resembling a dull chrome plating look, has come into use in recent years. For example, Patent Document 1 (Patent Publication No. 6715383) discloses an invention for an aqueous paint (see claim 9) made of indium with a purity of 95% or more and containing flaky (hereinafter referred to as "scale-like") indium particles having a specific particle size range.

[0005] In particular, automobile emblems are increasingly being fitted with sensors such as laser radar or millimeter-wave radar for obstacle detection, and flat indium carbide is available that can achieve both radio wave properties such as millimeter-wave transmission and a beautiful metallic luster color through a painting process alone. particle There are also known examples of forming metallic coating films using paints containing

[0006] For example, Patent Document 2 (Japanese Patent No. 6920509) relates to a metallic coating film and a method for forming the same, and describes a method of depositing flake indium particles having a specific particle size range on the surface of a substrate or on the surface of an undercoat layer provided on the substrate. particle and a solvent, and not containing a resin component, to form island portions; and forming a top coat layer on the surface on which the island portions are formed. particleOne particle or flake of said indium particle The invention discloses a metallic coating film in which a plurality of particles of the above at least partially overlap each other, and the top coat layer covers the surface of the island portions, and also covers the surface of the substrate or the surface of the undercoat layer in areas where the island portions are not present.

[0007] Furthermore, Patent Document 3 (Japanese Patent No. 7146311) describes a coating method for a substrate comprising an undercoat layer having a specific composition that is provided directly or indirectly on a substrate, and a thin film of vapor-deposited indium flakes (hereinafter referred to as "flake indium") having a specific particle size range that is provided on the undercoat layer. particle The invention discloses a coated article having a metal-containing coating layer in which the weight concentration (PWC) of metal-containing metals is 72.7% or more. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 6715383 [Patent Document 2] Patent No. 6920509 [Patent Document 3] Patent No. 7146311 [Patent Document 4] Patent No. 5950427 Summary of the Invention [Problem to be solved by the invention]

[0009] According to the invention disclosed in Patent Document 1, it is possible to obtain a coating film that can exhibit excellent metallic design with high gloss values, such as a gloss value of 150 or more at an incident angle of 20° and a gloss value (gloss value) of 170 or more at an incident angle of 60° (see claim 11), and furthermore, it is possible to obtain a coating film that can exhibit excellent metallic design with high gloss values, such as a gloss value of 150 or more at an incident angle of 60° and a gloss value (gloss value) of 170 or more at an incident angle of 60°. * value (total reflection) is 60 or more, a * Value is between -5 and 0.2, b *The value is between -1 and 8.5 (see claim 15), which provides the excellent effect of imparting a design comparable to chrome plating, a typical example of imparting a metallic design.

[0010] Also, the invention disclosed in Patent Document 2 provides a metallic coating film and a method for forming the same that can achieve both radio wave properties such as millimeter wave transmission and an aesthetic appearance with a metallic luster color through a coating process alone. Furthermore, the invention disclosed in Patent Document 3 makes it possible to obtain a metallic coating film with a 20° gloss value of 150 or more and a 60° gloss value of 170 or more, and a radio wave transmittance of 75% or more in the 24 GHz band and the 78 GHz band.

[0011] However, the metallic tone of the metallic coating films formed by the inventions disclosed in Patent Documents 1 to 3 is all formed by flake indium. particle Since the brightness is achieved by the indium itself, the brightness does not exceed the dull chrome plating level of the indium metal itself, and there is a demand for metallic coating films with a higher brightness.

[0012] The inventors have found that such flake indium particle As a result of various investigations to improve the brightness of metallic coating films formed using paints containing flaky indium particle The inventors discovered that by combining indium metal with silver nanoparticles, it is possible to enhance the brightness while maintaining the dull chrome-plated properties of indium metal itself, and have completed the present invention. That is, an object of the present invention is to provide a paint for forming an indium-toned coating film that has a high brightness and excellent mirror-finish design. [Means for solving the problem]

[0013] According to the present invention, flake indium particle and silver nano particle and a polymer dispersant and a volatile alcohol solvent. And, the flake indium particleThe silver nanoparticles particle The content ratio of the indium-toned coating film is 3% or more and 50% or less by mass.

[0014] In the paint for forming an indium-tone coating film of the present invention, scaly indium particle and silver nano particle This makes it possible to obtain an indium-tone coating film with a higher brightness (greater gloss value) while maintaining the dull chrome-plated properties of indium metal itself.

[0015] In addition, silver nano particle If ordinary silver particles are used instead, a mirror finish cannot be obtained, which does not lead to an improvement in gloss value. particle Does not contain flake indium particle A coating film is formed using a coating material comprising a polymer dispersant and a volatile alcohol solvent, and then flaky indium is applied to the surface of the coating film. particle Contains no silver nanoparticles particle Even if a coating film is formed by applying a paint containing a polymer dispersant and a volatile alcohol solvent, the indium-like appearance is lost and the film essentially becomes a silver coating, which is not preferable.

[0016] In addition, the polymer dispersant is a scaly indium particle and silver nano particle The alcohol solvent is necessary to disperse the scaly indium particles in the paint for forming an indium-toned coating film of the present invention in a stable state without agglomeration. particle and silver nano particle Since the coating material for forming an indium-toned coating film of the present invention can maintain good dispersibility and has good volatility, it is possible to form an indium-toned coating film with high brightness simply by applying the coating material for forming an indium-toned coating film of the present invention to various substrates and then drying it.

[0017] In the present invention, the term "scale-like" also includes those referred to as thin plate-like, flat plate-like, coated flake-like, etc. As a method for forming a coating film using the paint for forming an indium-toned coating film of the present invention, well-known methods such as spray coating, brush coating, and roller coater method can be used.

[0018] In the paint for forming an indium-tone coating film of the present invention, scaly indium particle Silver nanoparticles particle The content of flake indium is preferably 3% or more and 50% or less by mass. particle Silver nanoparticles particle When the content is less than 3% by mass, silver nanoparticles particle The effect of adding silver nanoparticles to improve brightness is small, and the brightness improvement effect saturates even if the amount exceeds 50%. particle However, the more preferable flake indium is expensive and therefore uneconomical. particle Silver nanoparticles particle The content ratio of is 10% or more and 40% or less by mass ratio.

[0019] In addition, in the paint for forming an indium-toned coating film of the present invention, silver nanoparticles particle It is preferable to use an alcohol solution prepared by dissolving a polymer dispersant having an acid value of 150 or less, which has a styrene-maleic anhydride resin structure in an alcohol solvent, and which is composed of a compound in which a portion of the maleic anhydride has been modified with a polyalkylene glycol having a terminal hydroxyl group or a polyalkylene glycol having a terminal amino group, and dispersing at least one silver compound selected from silver oxide and silver carbonate, and irradiating the alcohol solution with ultrasonic waves. particle is obtained in a dispersed state in an alcohol solvent containing a polymer dispersant, and has few impurities, especially silver nanoparticles. particle These can be used as they are in the preparation of the paint for forming the indium-toned coating film of the present invention without separation.

[0020] Furthermore, in the paint for forming an indium-toned coating film of the present invention, the alcohol solvent is preferably at least one selected from the group consisting of methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-methyl-1-propanol, 1-methoxy-2-propanol, and diacetone alcohol. These alcohol solvents are highly volatile and effectively function as reducing agents for reducing silver compounds using ultrasonic irradiation (sonochemical method), and also have excellent dissolving properties for polymer dispersants. In addition, these alcohol solvents have a fast evaporation rate at room temperature and are mild to the plastic substrate and primer layer on which the indium-toned coating film is formed, preventing erosion such as crazing of the substrate. This allows for the formation of an indium-toned coating film with excellent flatness and high brightness in a short period of time. A more preferred alcohol solvent is 1-methoxy-2-propanol (also known as propylene glycol-1-monomethyl ether or methoxypropanol). [Brief explanation of the drawings]

[0021] [Figure 1] 1 is a graph showing the relationship between the composition of paints for forming indium-toned coating films and gloss values ​​in Experimental Examples 1 to 10. [Figure 2] 1 is a graph showing the relationship between the composition of paints for forming indium-toned coating films in Experimental Examples 1 to 10 and the L* value in the CIE Lab color system. DETAILED DESCRIPTION OF THE INVENTION

[0022] The paint for forming an indium-toned coating film according to the present invention will be described in detail below using various experimental examples. However, the various experimental examples shown below are examples for embodying the technical concept of the present invention, and are not intended to limit the present invention to those shown in these experimental examples. The present invention can equally be applied to other embodiments included in the scope of the claims.

[0023] [Preparation of scaly indium particle dispersion] The scaly indium particle dispersion liquid used in common to all experimental examples was prepared as follows: Leaf Powder 49CJ-1120 (trade name, Oike Metallic Design Co., Ltd., average particle size: 0.2 to 0.5 μm), which is commercially available as a scaly indium particle paste (concentration 20% by mass), was dispersed in 1-methoxy-2-propanol so that the scaly indium particle content was 10% by mass, thereby preparing the scaly indium particle dispersion liquid used in common to all experimental examples.

[0024] [Preparation of silver nanoparticle dispersion] Using a 200ml glass beaker, 4g of polymer dispersant Disperbyk 2015 (40% non-volatile content, acid value 10, manufactured by BYK) was dissolved in 100g of 2-propanol (isopropyl alcohol) and 25g of silver oxide powder was suspended. The acid value of the non-volatile content of this polymer dispersant was 25, and the polymer dispersant content relative to the silver oxide was (4 x 0.4 / 25) x 100 = 6.4% by mass. Disperbyk 2015 has a styrene-maleic anhydride resin structure, with a portion of the maleic anhydride modified with polyalkylene glycol at the terminal hydroxyl groups.

[0025] Next, this suspension was irradiated at 20 kHz for 2 hours at room temperature of 15-17°C using an ultrasonicator H3 650 (Kawajiri Machinery Co., Ltd.) to induce a sonochemical reaction. The suspension was then filtered through a 1 μm filter to obtain a brown silver nanoparticle dispersion. A surface plasmon band originating from the silver nanoparticles was observed around 425 nm in this silver nanoparticle dispersion. This silver nanoparticle dispersion was then diluted with 1-methoxy-2-propanol to a silver nanoparticle content of 10% by mass, yielding the silver nanoparticle dispersion used in the experimental examples. The method for preparing this silver nanoparticle dispersion is in accordance with the method disclosed in Patent Document 4, and is a known method.

[0026] [Experimental Example 1] In Experimental Example 1, the flake indium prepared as described above was used. particleThe dispersion was used as is to spray paint a black ABS (acrylonitrile-butadiene-styrene copolymer resin) plate and dried at 80°C for 30 minutes to prepare a coated sample of Experimental Example 1. The indium concentration in the coated sample of Experimental Example 1 corresponds to 10 mass%. The gloss value of the coated sample of Experimental Example 1 was measured using Micro-Gloss 60 (trade name, manufactured by BYK), and the L in the CIE Lab color system was measured using Color Reader CR-10Plus (trade name, manufactured by Konica Minolta). * The results are shown in Table 1 together with the composition of the coated samples.

[0027] [Experimental Example 2] In Experimental Example 2, 100 g of the scaly indium particle dispersion liquid prepared as described above and 3 g of the silver nanoparticle dispersion liquid prepared as described above were mixed to obtain the scaly indium particle dispersion liquid used in Experimental Example 2. particle and silver nano particle A dispersion was prepared, and a coated sample of Experimental Example 2 was prepared in the same manner as in Experimental Example 1, and the gloss value was measured. A coated sample of Experimental Example 1 was prepared from the coated sample of Experimental Example 2. The indium concentration in the coated sample of Experimental Example 2 was equivalent to 9.7% by mass, and the flaky indium particle Silver nanoparticles particle The content ratio of was 3% by mass. The results are shown in Table 1 together with the composition of the coated sample.

[0028] [Experimental Example 3] In Experimental Example 3, 100 g of the scaly indium particle dispersion liquid prepared as described above was mixed with 5 g of the silver nanoparticle dispersion liquid also prepared as described above, and the scaly indium particle dispersion liquid used in Experimental Example 2 was obtained. particle and silver nano particle A dispersion was prepared, and a coated sample of Experimental Example 3 was prepared in the same manner as in Experimental Example 1, and the gloss value was measured. The indium concentration in the coated sample of Experimental Example 3 was equivalent to 9.5% by mass, and the flaky indium particle Silver nanoparticles particle The content ratio of was 5% by mass. The results are shown in Table 1 together with the composition of the coated sample.

[0029] [Experimental Example 4] In Experimental Example 4, 100 g of the scaly indium particle dispersion liquid prepared as described above and 10 g of the silver nanoparticle dispersion liquid prepared as described above were mixed to obtain the scaly indium particle dispersion liquid used in Experimental Example 4. particle and silver nano particle A dispersion was prepared, and a coated sample of Experimental Example 4 was prepared in the same manner as in Experimental Example 1, and the gloss value was measured. The indium concentration in the coated sample of Experimental Example 4 was equivalent to 9.1% by mass, and the flaky indium particle Silver nanoparticles particle The content ratio of was 10% by mass. The results are shown in Table 1 together with the composition of the coated sample.

[0030] [Experimental Example 5] In Experimental Example 5, 100 g of the scaly indium particle dispersion liquid prepared as described above and 20 g of the silver nanoparticle dispersion liquid prepared as described above were mixed to obtain the scaly indium particle dispersion liquid used in Experimental Example 5. particle and silver nano particle A dispersion was prepared, and a coated sample of Experimental Example 5 was prepared in the same manner as in Experimental Example 1, and the gloss value was measured. The indium concentration in the coated sample of Experimental Example 5 was equivalent to 8.3 mass %. particle Silver nanoparticles particle The content ratio of was 20% by mass. The results are shown in Table 1 together with the composition of the coated sample.

[0031] [Experimental Example 6] In Experimental Example 6, 100 g of the scaly indium particle dispersion liquid prepared as described above and 30 g of the silver nanoparticle dispersion liquid prepared as described above were mixed to obtain the scaly indium particle dispersion liquid used in Experimental Example 6. particle and silver nano particle A dispersion was prepared, and a coated sample of Experimental Example 6 was prepared in the same manner as in Experimental Example 1, and the gloss value was measured. The indium concentration in the coated sample of Experimental Example 6 was equivalent to 7.7% by mass, and the flaky indium particle Silver nanoparticles particleThe content ratio of was 30% by mass. The results are shown in Table 1 together with the composition of the coated sample.

[0032] [Experimental Example 7] In Experimental Example 7, 100 g of the scaly indium particle dispersion liquid prepared as described above and 40 g of the silver nanoparticle dispersion liquid prepared as described above were mixed to obtain the scaly indium particle dispersion liquid used in Experimental Example 7. particle and silver nano particle A dispersion was prepared, and the gloss value of a coated sample of Experimental Example 7 was measured in the same manner as in Experimental Example 1. The indium concentration in the coated sample of Experimental Example 7 was 7.1% by mass, and the flaky indium particle Silver nanoparticles particle The content ratio of was 40% by mass. The results are shown in Table 1 together with the composition of the coated sample.

[0033] [Experimental Example 8] In Experimental Example 8, 100 g of the scaly indium particle dispersion liquid prepared as described above and 50 g of the silver nanoparticle dispersion liquid prepared as described above were mixed to obtain the scaly indium particle dispersion liquid used in Experimental Example 8. particle and silver nano particle A dispersion was prepared, and the gloss value of a coated sample of Experimental Example 8 was measured in the same manner as in Experimental Example 1. The indium concentration in the coated sample of Experimental Example 8 was 6.7% by mass, and the flaky indium particle Silver nanoparticles particle The content ratio of was 50% by mass. The results are shown in Table 1 together with the composition of the coated sample.

[0034] [Experimental Example 9] In Experimental Example 8, 100 g of the scaly indium particle dispersion liquid prepared as described above and 60 g of the silver nanoparticle dispersion liquid prepared as described above were mixed to obtain the scaly indium particle dispersion liquid used in Experimental Example 9. particle and silver nano particle A dispersion was prepared, and the gloss value of a coated sample of Experimental Example 9 was measured in the same manner as in Experimental Example 1. The indium concentration in the coated sample of Experimental Example 9 was 6.3% by mass, and the flaky indium particle Silver nanoparticles particle The content ratio of was 60% by mass. The results are shown in Table 1 together with the composition of the coated sample.

[0035] [Experimental Example 10] In Experimental Example 10, 100 g of the scaly indium particle dispersion liquid prepared as described above and 70 g of the silver nanoparticle dispersion liquid prepared as described above were mixed to obtain the scaly indium particle dispersion liquid used in Experimental Example 10. particle and silver nano particle A dispersion was prepared, and the gloss value was measured by preparing a coated sample of Experimental Example 10 in the same manner as in Experimental Example 1. The indium concentration in the coated sample of Experimental Example 10 was equivalent to 5.9 mass %. particle Silver nanoparticles particle The content ratio of was 70% by mass. The results are shown in Table 1 together with the composition of the coated sample.

[0036] Scaly indium in the coating samples of Experimental Examples 1 to 10 particle Silver nanoparticles particle The content ratio and measured gloss value and L * The values ​​are summarized in Table 1. Furthermore, the flaky indium in the coating sample particle Silver nanoparticles particle The relationship between the content of indium and the measured gloss value is shown in Figure 1. particle Silver nanoparticles particle The content ratio and measured L * The relationship between the values ​​is shown in Figure 2.

[0037] [Table 1]

[0038] The results shown in Table 1 and Figure 1 reveal the following: In terms of gloss value, the use of silver nanoparticles in the paint for forming an indium-toned coating film particle In the case of the coating film in Experimental Example 1, which does not contain silver nanoparticles, particleIn contrast, the gloss value of the coating film of Experimental Examples 2 to 10, which contains silver nanoparticles, is lower than that of the coating film of Experimental Examples 2 to 10, which contains silver nanoparticles. particle The gloss values ​​of the coating films of Experimental Examples 2 to 10 containing silver nanoparticles are greater than that of the coating film of Experimental Example 1. particle The gloss value of the coating containing silver nanoparticles is particle The increase is proportional to the content of silver nanoparticles. particle Experimental example 1 does not contain silver nanoparticles. particle The difference between the silver nanoparticles in Experimental Example 1 and Experimental Example 2, where the silver nanoparticle content is 3%, is the largest. particle The gloss value decreases as the content ratio increases, and the coating films of Experimental Examples 9 and 10 have substantially the same gloss value.

[0039] In addition, the L* value is determined by the presence of silver nanoparticles in the paint for forming the indium-tone coating film. particle The increase in the proportion of silver nanoparticles is proportional to the increase in the proportion of silver nanoparticles. particle When the content exceeds 50%, the L* value is saturated, and the coating films of Experimental Examples 8 to 10 have substantially the same L* value.

[0040] From the above results, it is clear that the scale-like indium in the coating film particle Silver nanoparticles particle The content of silver nanoparticles is less than 3% by mass. particle The effect of adding silver nanoparticles to improve gloss is small, and even if the amount exceeds 50%, the effect of improving gloss is saturated. particle However, since the indium content is expensive, it is uneconomical. Therefore, it is preferable that the upper limit is 50% or less. particle Silver nanoparticles particle If the content is less than 10%, silver nano particle The gloss value of the coating film decreases significantly as the content of flake indium decreases. particle Silver nanoparticles particle The content ratio of is thought to be 10% or more and 40% or less by mass.

[0041] Similarly, when viewed from the perspective of the L* value, the scale-like indium in the coating film particle Silver nanoparticles particle The content of silver nano particle As the content of indium increases, the L* value also increases, but even if the content exceeds 40%, the effect of improving the L* value saturates. particle Silver nanoparticles particle Between 40% and 50% of the silver nanoparticles particle Since the increase in the gloss value of the coating film with increasing content is small, the upper limit is 50% or less, and silver nano particle Since this is effective, and also considering economic efficiency, it is understood that 40% or less is preferable.

[0042] Although the term "glossiness" is used to describe metallic designs, it is difficult to express the sense of brightness numerically. In addition, since both the gloss value and the L* value are generally values ​​that depend on the measuring device, it is difficult to uniquely determine the L* value from the gloss value, and conversely, the gloss value from the L* value. However, as an index of the sense of brightness, it can be shown that brightness is improved by a high gloss value and a high L* value (brightness). Therefore, in the present invention, the measurement results of the gloss value and the L* value are comprehensively judged, and further, the silver nanoparticles are used to judge the sense of brightness. particle Taking into consideration the economical aspect that indium is expensive, the preferred flaky indium content in the coating film is particle Silver nanoparticles particle The content ratio of is considered to be 3% or more and 50% or less by mass, and more preferably 10% or more and 40% or less.

Claims

1. A paint for forming an indium-tone coating film, comprising scaly indium particles, silver nanoparticles, a polymer dispersant, and a volatile alcohol solvent, A paint for forming an indium-toned coating film, characterized in that the content ratio of the silver nanoparticles to the scaly indium particles is 3% or more and 50% or less by mass ratio.

2. 2. The paint for forming an indium-toned coating film according to claim 1, wherein the volatile alcohol solvent is at least one selected from the group consisting of methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-methyl-1-propanol, and 1-methoxy-2-propanol.

Citation Information

Patent Citations

  • Manufacturing method of metallic luster coat

    JP2009106903A

  • Flaky indium particle, method of manufacturing the same, luminous pigment, aqueous coating material, aqueous ink, and coated film

    JP2020132998A

  • Metallic tone coated film, molding having the same, and method for forming metallic tone coated film

    JP2021172048A

  • Coated object, coated object production method, and paint set

    WO2022264188A1